Criminological characterization of domestic violence: scientific article - Temirkanova, Д.К.; Smatlaev, Б.М.; Мukanov, М.Р. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
In order to understand and prevent domestic violence, it is necessary to analyze specific cases of domestic violence. Criminological characterization of domestic violence includes analysis of the specifics of this phenomenon, its signs, factors contributing to its commission. The development of effective measures to prevent domestic violence must take into account all the data obtained during such a criminological analysis. The article uses a dialectical approach to cognition to study the criminological aspects of domestic violence. The study was conducted using a comprehensive methodological toolkit, including general scientific, private scientific and empirical research methods. The author has analyzed the statistics and materials of criminal and administrative cases on offenses in the family and domestic sphere, considered by the courts of Kostanay region for the period 2019-2023. The work includes the characterization of the main criminological indicators of domestic violence, taking into account such factors as place, time and other circumstances of committing crimes and offenses. The obtained data allow to develop more effective preventive measures taking into account the presented criminological characterization of domestic violence. As a result of the conducted research the low effectiveness in combating domestic violence of the legislatively established prohibition of cohabitation with the victim for perpetrators of domestic violence, as well as protective prescriptions due to insufficient practical measures to ensure. In this regard, possible solutions are presented, among which the most appropriate one is highlighted.